2014
DOI: 10.1155/2014/258291
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Genital HSV-2 Shedding among Women during Labor in Soweto, South Africa

Abstract: Background. Despite high herpes simplex virus type 2 (HSV-2) incidence and prevalence among women in Africa, we are unaware of published neonatal herpes reports. To assess neonatal HSV transmission potential in South Africa, we investigated the frequency of the strongest risk factors: HSV acquisition in late pregnancy and HSV shedding during labor. Methods. Women admitted in early labor to a hospital in Soweto underwent HSV serologic testing and genital swab collection for HSV PCR. HSV-2 seronegative women wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
1
20
1
1
Order By: Relevance
“…The prevalence varies from country to country, which is well illustrated by the fact that in Nigeria 99.4 % of pregnant women were seropositive for anti‐HSV‐1 and HSV‐2 IgG antibodies, while in South Africa the seroprevalence of HSV‐2 infection was 58.7 %. Ethiopia had the lowest rate of African countries, with 32.1 % . Similar to Ethiopia, the overall weighted prevalence of HSV‐2 was 31.4 % in Haiti, while in Korea, Kim et al.…”
Section: Prevalence Incidence and Burden Of The Diseasementioning
confidence: 92%
“…The prevalence varies from country to country, which is well illustrated by the fact that in Nigeria 99.4 % of pregnant women were seropositive for anti‐HSV‐1 and HSV‐2 IgG antibodies, while in South Africa the seroprevalence of HSV‐2 infection was 58.7 %. Ethiopia had the lowest rate of African countries, with 32.1 % . Similar to Ethiopia, the overall weighted prevalence of HSV‐2 was 31.4 % in Haiti, while in Korea, Kim et al.…”
Section: Prevalence Incidence and Burden Of The Diseasementioning
confidence: 92%
“…Using the U L _U S file, Circos software (version 0.64) was used to create a genetic map showing the presence of base substitutions in the open reading frame (coding) regions of the genome (75). Among all identified base substitutions from the 38 sequences from unique participants and SD90e, only base substitutions with a valid base call at that position in at least 20 of the sequences were included.…”
Section: Methodsmentioning
confidence: 99%
“…The present study found a high prevalence of HSV-1 from urine samples compared to HSV-2 (48.3 and 10.7%, respectively) when real-time PCR assay was used. A study conducted in Soweto, South Africa showed that 17% of pregnant women shed HSV2 (Perti et al, 2014). Similarly, studies conducted in South West of Iran showed that the HSV-1 sero-prevalence (79.2%) was higher than HSV-2 (23.3%) (Tayyebi and Sharifi, 2010).…”
Section: Discussionmentioning
confidence: 97%